2009
DOI: 10.1002/ange.200805241
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery by an Enzyme‐Mediated Cyclization of a Lipid Prodrug with Unique Bilayer‐Formation Properties

Abstract: Liposomale Wirkstofftransportsysteme, in denen Vorstufen durch krankheitsspezifische Enzyme aktiviert werden, haben ein großes Potenzial für die Therapie von Erkrankungen wie Krebs. Eine neuartige Wirkstoffvorstufe auf Phospholipidbasis kann stabile kleine unilamellare Vesikel aufbauen (siehe Bild). Die Aktivierung dieser Vesikel durch das Enzym sPLA2 löst eine Cyclisierungsreaktion aus, die zur Freisetzung des Wirkstoffs führt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
(6 reference statements)
0
11
0
1
Order By: Relevance
“…They further applied their discovery to create a lipid-capsaicin prodrug. The prodrug was able to form small unilamellar vesicle (SUV), and the SUV was stable in the bloodstream, but could specifically respond to PLA2 to release the covalently attached anticancer drug by PLA2-promoted intramolecular cyclization [99]. …”
Section: Enzymatic Activationmentioning
confidence: 99%
“…They further applied their discovery to create a lipid-capsaicin prodrug. The prodrug was able to form small unilamellar vesicle (SUV), and the SUV was stable in the bloodstream, but could specifically respond to PLA2 to release the covalently attached anticancer drug by PLA2-promoted intramolecular cyclization [99]. …”
Section: Enzymatic Activationmentioning
confidence: 99%
“…Although the concept of Sn2 phospholipid prodrugs had never been considered for targeted drug delivery associated with CFDD, precedence for the formation of Sn2 phospholipid prodrugs was initially reported by David Thompson et al 37 in the context of triggered release mechanisms. Later Thomas Lars Andresen and colleagues [38][39][40][41][42][43][44][45][46][47][48] pursued an approach to deliver chemotherapeutics as Sn2 prodrugs via untargeted liposomes. They anticipated that increased liberation of phospholipases by cancers would trigger release of the compounds in the proximity of a tumor increasing the local drug bioavailability.…”
Section: Phospholipid Sn2 Prodrugs With Liposomesmentioning
confidence: 99%
“…However, thioester hydrolysis by the enzyme occurred at a substantially lower rate than the catalytic hydrolysis of natural substrate (Balet et al, 1988; Reynolds et al, 1991). In addition, subsequent research indicated that the PLA 2 -catalyzed thioester hydrolysis is likely to proceed via a different reaction mechanism (Linderoth et al, 2009). …”
Section: Introductionmentioning
confidence: 99%